25 años de la Revista Cuestiones Económicas del Banco Central del Ecuador - Cartagenova Miño, Carlos (2004)
In the year of 1979 the Economic Questions Magazine of the Central Bank of Ecuador was published as a quarterly publication. The modus cogitandi or the raison d'être of the magazine, according to its first issue, is that of "... from the economic angle, to analyze the realities of man and of Ecuadorian society." * The Economic Issues Magazine that, over time, it has become the academic body of the Central Bank of Ecuador, it was born with the intention of "supporting the development of socioeconomic research in our country in order to enrich it with new contributions